Discrete populations of isotype-switched memory B lymphocytes are maintained in murine spleen and bone marrow - René Riedel (Nature Portfolio, 2020)
Memory B cells are important for protecting the host from pathogen rechallenge, but their properties and locations remain ill-defined. Here the authors show, using single-cell transcriptomics and repertoire analyses, that mouse spleen and bone marrow host distinct populations of isotype-switched memory B cells to potentially optimize for rapid recall responses.